Flash Profile for rapid descriptive analysis in sensory characterization of passion fruit juice - Montanuci, Flávia Daiana; Marques, Diego Rodrigues; Monteiro, Antonio Roberto Giriboni (Acta Scientiarum. Technology, 2015)
The Flash Profile is a descriptive analysis method derived from Free-Choice Profile, in which each taster chooses and uses his/her own words to evaluate the product while comparing several attributes. Four passion fruit juices were analyzed, two juices were produced with concentrated juice, one with pulp and one with reconstituted juice; all juices had different levels of sugar, some had gum and dyes. This study aimed to evaluate the physicochemical properties (color, titratable acidity and solid content) as well as sensory analysis like Flash profile and affective test. In physicochemical characterization and in Flash Profile, the juice A (pulp) had higher solid content and consistence, the juice B (concentrated juice) was the least acidic and presented the lowest value of soluble solids and presented strong aroma and flavor of passion-fruit, the juice C (reconstituted juice) was pale yellow and showed artificial flavor and the juice D (concentrated juice) was the most acidic, consistent with the natural flavor. In the acceptance test, all the juices scored 5-6, indicating that panelists tasters neither liked nor disliked. Flash Profile proved to be an easy and rapid technique showing a good correlation between panelists and the attributes and confirmed the results of physicochemical characterization. Â 